2021
DOI: 10.1029/2020gl090293
|View full text |Cite
|
Sign up to set email alerts
|

A New Reconstruction for Permian East Gondwana Based on Zircon Data From Ophiolite of the East Australian Great Serpentinite Belt

Abstract: Eastern Australia preserves a very detailed record of complex convergent plate margin activity along paleo-Pacific Gondwana. Broadly, the margin is typified by cycles of extension and contraction (e.g., Collins, 2002). Extension cycles occur during brief phases of slab retreat, with resultant metamorphic complexes, S-type granitic magmatism, extensional back-arc basins on the continent with arcs forming offshore. These phases are followed by contraction and a renewal of continental arc magmatism (e.g.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 83 publications
(149 reference statements)
0
11
0
Order By: Relevance
“…In contrast, Milan et al. (2021) have recently found that the age of plagiogranite dykes, intruded into a relatively coherent block of gabbro (18 km 2 ), is Early Permian (∼280 Ma). The conclusion by Milan et al.…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…In contrast, Milan et al. (2021) have recently found that the age of plagiogranite dykes, intruded into a relatively coherent block of gabbro (18 km 2 ), is Early Permian (∼280 Ma). The conclusion by Milan et al.…”
Section: Discussionmentioning
confidence: 90%
“…However, Milan et al. (2021) have recently suggested that the age of this ocean is much younger than previously thought, based on the age of plagiogranite dykes (∼280 Ma) intruded into a larger (∼18 km 2 ) block of ophiolite.…”
Section: Geological Settingmentioning
confidence: 88%
See 1 more Smart Citation
“…Two major are-up cycles are identi ed along the arc at c. 290-280 Ma (30 km 3 /my per km) and c. 260-245 Ma (63 km 3 /my per km) that punctuate the background low-volume magmatism along the margin (5-10 km 3 /my per km: Fig. 3) 21 . The c. 290-280 Ma peak is related to back-arc extension and crustal reworking 22 .…”
Section: Eastern Australia Permian Are-upmentioning
confidence: 99%
“…Crystallisation of parts of the GSB has been constrained to the early Cambrian based on a U-Pb age of zircon in plagiogranite associated to the serpentinite sequence (530 ± 6 Ma; Aitchison and Ireland, 1995) but more recent zircon dating of serpentinite north of Woodsreef suggest formation ages of ~283-277 Ma (Milan et al, 2020). The GSB was emplaced along the Peel-Manning Fault during the early Permian, as indicated by thermal alteration by the Bundarra Plutonic Suite (267.2 ± 1.4 Ma; Cawood et al, 2011) and serpentinite interleaving with the Sakmarian Kensington Formation (Vickery et al, 2010).…”
Section: Great Serpentinite Beltmentioning
confidence: 99%